New Scale-up Technologies for Hydrogenation Reactions in Multipurpose Pharmaceutical Production Plants - Thierry Furrer (Swiss Chemical Society, 2021)
The classical scale-up approach for hydrogenation reaction processes usually includes numerous laboratory- and pilot-scale experiments. With a novel scale-up strategy, a significant number of these experiments may be replaced by modern computational simulations in combination with scale-down experiments. With only a few laboratory-scale experiments and information about the production-scale reactor, a chemical process model is developed. This computational model can be used to simulate the production-scale process with a range of different process parameters. Those simulations are then validated by only a few experiments in an advanced scale-down reactor. The scale-down reactor has to be geometrically identical to the corresponding production-scale reactor and should show a similar mass transfer behaviour. Closest similarity in terms of heat transfer behaviour is ensured by a sophisticated 3D-printed heating/cooling finger, offering the same heat exchange area per volume and overall heat-transfer coefficient as in production-scale. The proposed scale-up strategy and the custom-designed scale-down reactor will be tested by proof of concept with model reactions. Those results will be described in a future publication. This project is an excellent example of a collaboration between academia and industry, which was funded by the Aargau Research Fund. The interest of academia is to study and understand all physical and chemical processes involved, whereas industry is interested in generating a robust and simple to use tool to improve scale-up and make reliable predictions.